Nitrogen dynamic and precise management to predict corn yield in tropical upland acid soils - A. Kasno; A.A. Rivaie; C. Tafakresnanto; E. Pratiwi; E. Karmawati; A.F. Siregar; M. Hatta; M.T. Sutriadi (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: To meet the needs of the global population (9.7 billion people) until 2050, a 45 percent increase in corn production is required. Efforts to enhance corn production may be informed, among others, precise N management. This research aims to determine nitrogen dynamics and precise nitrogen nutrient management in corn cultivation using a leaf chlorophyll meter and nitrogen response tests to predict corn yield in tropical upland acid soils.METHODS: This research was conducted in an Ultisol and verified in an Oxisol. The trial was arranged in a randomized completely block design with eight treatments: 0, 45, 90, 135, 180, 225, 270, and 315 kilograms nitrogen per hectare, repeated three times. The chlorophyll content of corn leaves was measured at 45 and 60 days after planting, using a chlorophyll meter. Data analysis was carried out on vegetative growth and yield, as well as nitrogen content in the soil, leaf, and grains.FINDINGS: The study found that the application of nitrogen fertilizer at the rate of 180 kilograms per hectare can alter nitrate concentrations in soil and significantly increases nitrogen uptake, growth, and corn yield. The maximum nitrogen fertilizer rate was 274.5 kilograms nitrogen per hectare, with corresponding chlorophyll meter readings of 52.8 and a corn yield of 8.58 tons per hectare. The corn yield at the rate of maximum nitrogen fertiliser (8.58 tons per hectare) was not significantly different from that at the rate of 180 kilogrammes nitrogen per hectare (8.54 tons per hectare). There was a strong correlation between corn yields and chlorophyll meter values with correlation coefficient of 0.92.CONCLUSION: The study revealed that applying nitrogen fertilizer at the medium rate of 180 kilograms per hectare can lead to an increase in nitrogen uptake, growth, and corn yield on tropical upland acid soils. There was not a significant difference in corn yield between the rate of nitrogen fertilization at 180 kilograms per hectare and the maximum rate of 274.5 kilograms nitrogen per hectare. In terms of sustainable agriculture management, the medium rate of 180 kilograms nitrogen is recommended for maximizing crop yield on the upland acid soils and minimizing potential environmental impacts associated with excessive use of fertilizers. There is a strong correlation between leaf chlorophyll meter readings and corn yield, suggesting the chlorophyll meter can serve as a reliable tool in the study site in determining optimal fertilizer rates.